Violence at School and the Well-Being of Teachers. The Importance of Positive Relationships - De Cordova, Federica; Berlanda, Sabrina; Pedrazza, Monica; Fraizzoli, Marta (Frontiers in Psychology, 2019)
In the discipline of positive psychology, “well-being” is considered a fundamental aspect of “human flourishing”. Inherent to this multidimensional model are emotional, psychological and social forms of well-being, which can be grounded in positive relationships in the work environment. Exploring well-being and flourishing in these terms promises to transform our theoretical approach to such issues, allowing researchers to focus primarily on those elements that help sustain the process of flourishing, rather than on negative environmental features that should be avoided if possible. Within this broader discussion, the question of well-being among teachers emerges as a common concern throughout the world, one that merits greater academic attention given that it has significant consequences for the educational environment offered to students and their ability to learn. Literature suggests that teachers are increasingly exposed to violent behaviours on the part of students and/or their parents, to the extent that misbehaviour and aggression is one of the most serious work-related stress factors affecting the teaching profession, one that is capable of seriously reducing teachers’ occupational well-being and preventing them from building positive relationships in the classroom. Violence directed against teachers is an issue of global significance. Existing studies have attempted to characterise the contexts in which violence occurs, and its negative impact on both the individuals involved and the broader educational climate. Less attention has been devoted to the capacity of teachers to deal with violence and develop a more resilient mindset. The positive psychology perspective focuses on well-being as a multidimensional construct wherein psychosocial and physical comfort does not simply arise if there is an absence of suffering and violence. Rather, according to this model, such experiences can be counteracted by a capacity to endure and build positive environments. With these considerations in mind, our study presents data gathered in primary and secondary schools in northern Italy. A total 475 teachers completed an online, self-report questionnaire. The results indicate that teachers can experience occupational well-being even if they are subjected to aggressive behaviours. Supportive leadership and good relationships with colleagues may be considered valuable resources for fostering positive emotions and human flourishing.